Answer:
x = -4/5
y = 9/5
Explanation:
-3y + 2x = -7
8x - 3y = -1
make one of the equations y=....
-3y + 2x = -7
-3y = -7 - 2x
y = (-7 - 2x)/3
now put (-7 - 2x)/3 where y is in the other equation
8x - 3y = -1
8x - 3((-7 - 2x)/3) = -1
8x - 1*(-7 - 2x) = -1
8x + 7 + 2x = -1
solve for x
8x + 7 + 2x = -1
8x+2x = -8
10x = -8
x = -8/10
x = -4/5
now put -8/10 in one of the equations to get what y is
-3y + 2x = -7
-3y + 2(-8/10) = -7
-3y - 16/10 = -7
-3y = -7 + 16/10
-3y = -70/10 + 16/10
-3y = -54/10
y = -54/10 * -1/3
y = 18/10
y = 9/5